Contents of the Gradual Kraków, AiBKKK, Ms 45 .......... 93 - Ferfoglia, Susi; Baran, Wojciech (Graduał wawelski (Kraków, AiBKKK, Ms 45): Studium przypadku, 2025)
This article examines the contents of the Graduale Kraków, AiBKKK, Ms 45. Although this manuscript’s content was previously elaborated by Sister Alicja Jończyk in her 1975 study, the scholarly literature has not yet analyzed its content in relation to the international identification numbers in the “Cantus Index” database. Moreover, previous studies have not identified the musical modes of the compositions it contains or provided a transcription of the rubrics for the celebration of the Triduum Sacrum and the Vigil of Pentecost. This study aims to fill these gaps in the literature.